PPAR γ/Nnat/NF-κB Axis Involved in Promoting Effects of Adiponectin on Preadipocyte Differentiation - Wenkai Yang; Wenjin Yuan; Xinghua Peng; Meiling Wang; Jie Xiao; Cheng Wu; Lie Luo (Mediators of Inflammation)
A previous study has demonstrated that adiponectin (APN) could promote preadipocyte differentiation, and the present study further explored its mechanism. 3T3-L1 cells were infected with adenovirus holding human adiponectin gene apM1 and mouse neuronatin (Nnat) shRNA and initiated differentiation while coculturing with mature adipocytes stimulated with LPS. After 8 days, preadipocyte differentiation was observed by Oil Red O staining. Real-time quantitative PCR was used to evaluate mRNA expression levels of monocyte chemoattractant protein-1 (MCP-1), interleukin- (IL-) 6, IL-8, and tumor necrosis factor α (TNF-α). The levels of reactive oxygen species (ROS), total antioxidant capacity (T-AOC), malondialdehyde (MDA), and superoxide dismutase (SOD) in 3T3-L1 cells were detected. Western blotting was done to quantify the protein expression levels of Nnat, peroxisome proliferator-activated receptor (PPAR) γ, p65, and inhibitor of nuclear factor κB (IκB) α. Results demonstrated that APN overexpression markedly increased preadipocyte differentiation; inhibited gene expression of MCP-1, IL-6, IL-8, and TNF-α; reduced ROS and MDA release; increased T-AOC and SOD levels; upregulated Nnat, PPAR γ, and IκB α protein expressions; and downregulated p65 protein expression under LPS stimulation. However, the effects of APN were markedly attenuated when Nnat expression was knocked down. Taken together, the present study provided evidences that the effects of APN on promoting preadipocyte differentiation under inflammatory conditions via anti-inflammation and antioxidative stress may be regulated by the PPAR γ/Nnat/NF-κB signaling pathway.